PEREMPUAN – PEREMPUAN DI DEWAN PERWAKILKAN RAKYAT DAERAH KABUPATEN SAROLANGUN 2004 – 2024 - Yana, Fika; Karmela, Siti Heidi; Azmi, Ulul (Universitas Batanghari Jambi, 2025)
This research is a historical research with the theme of Women's History. his study aims to describe women's involvement in local politics in the Sarolangun Regency DPRD throughout 2004 – 2024. The method used in this research is a historical research method consisting of several stages, namely heuristics, criticism, interpretation, and historiography. The primary source used in this research is an interview with female officials in the Sarolangun Regency DPRD. While the secondary sources used are books, theses, journals and internet sources. The results of the study show that women can also have the same place as men with a point of view that can be considered in the political world, being a female official is also a challenge in managing the household and as a public worker. The research findings show that female officials have their own unique ways of managing household chores and their roles as public officials.